Correction of the fundamental voice frequency using tactile and visual feedback - Alves, Rodrigo Leone (2015)
People who are deaf or hard of hearing require correction of the fundamental frequency that usually is achieved by help of a phonodiologist. The work of the phonodiologist can be however strongly reduced by using appropriate devices that can help the patient to train the voice positioning. This paper reports the development of such a system based on FPGA's technology that providing tactile and visual feedback. Contrary to the feedback from the phonodiologist that is usually relative, the feedback provided by a device can be provided in absolute terms. This feature can improve the learning process that however needs the initial learning provided by the phonodiologist.